2006
DOI: 10.1016/j.rmed.2005.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sublingual immunotherapy with high-dose mite extracts in asthma: A multi-center, double-blind, randomized, and placebo-controlled study in Taiwan

Abstract: Sublingual immunotherapy (SLIT) has been recommended as a viable alternative to subcutaneous injection therapy in the treatment of airway allergies, though more data is needed from well-controlled studies for documenting its efficacy in different ethnic populations. Ninety-seven children (age range 6-12 years), mild-to-moderate asthma with a single sensitization to mite allergen, were enrolled from 5 medical centers in Taiwan to evaluate the efficacy and safety of SLIT with standardized mite extracts, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 21 publications
2
111
1
2
Order By: Relevance
“…[22][23][24][32][33][34][35]37,38 Seven studies evaluated dust mite allergen. [22][23][24][32][33][34]38 The SLIT-treated children in the placebo-controlled studies demonstrated moderate to strong improvement in asthma symptoms. The risk of bias was low in 3 studies.…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][32][33][34][35]37,38 Seven studies evaluated dust mite allergen. [22][23][24][32][33][34]38 The SLIT-treated children in the placebo-controlled studies demonstrated moderate to strong improvement in asthma symptoms. The risk of bias was low in 3 studies.…”
Section: Asthmamentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29]32,33,[35][36][37] Six studies evaluated dust mite allergen. [22][23][24][25][26]32 The placebo-controlled studies demonstrated significant reductions in medication use in the SLIT group relative to the placebo group, with moderate to strong magnitudes of effect in patients with asthma and/or rhinitis. The magnitudes of effect could not be determined in 7 studies.…”
Section: Medication Scoresmentioning
confidence: 99%
“…In one of the studies, a subsequent post hoc analysis by asthma severity revealed significant clinical benefit in the AIT group with moderate, persistent asthma at baseline with 401-800 μg budesonide/day; with greater achievement of well-control asthma and totally controlled asthma (236). In another study, global assessment of asthmatic symptom by patient and physician, the primary outcome measure, was improved after ASIT but not placebo treatment (233).…”
Section: Asthma Controlmentioning
confidence: 98%
“…The efficacy of AIT in asthma is measured using symptom scores, medication scores, as well as lung function test (55,134,(233)(234)(235). The symptom and medication scores are frequently used as primary endpoints in AIT trials.…”
Section: Asthma Controlmentioning
confidence: 99%
See 1 more Smart Citation